The leishmaniases in Kenya: A scoping review. - Grace Grifferty; Hugh Shirley; Katherine O'Brien; Jason L Hirsch; Adrienne M Orriols; Kiira Lani Amechi; Joshua Lo; Neeharika Chanda; Sarra El Hamzaoui; Jorja Kahn; Samantha V Yap; Kyleigh E Watson; et al. (Public Library of Science (PLoS), 2023)
Background The leishmaniases are a group of four vector-borne neglected tropical diseases caused by 20 species of protozoan parasites of the genus Leishmania and transmitted through a bite of infected female phlebotomine sandflies. Endemic in over 100 countries, the four types of leishmaniasis-visceral leishmaniasis (VL) (known as kala-azar), cutaneous leishmaniasis (CL), mucocutaneous leishmaniasis (MCL), and post-kala-azar dermal leishmaniasis (PKDL)-put 1.6 billion people at risk. In Kenya, the extent of leishmaniasis research has not yet been systematically described. This knowledge is instrumental in identifying existing research gaps and designing appropriate interventions for diagnosis, treatment, and elimination. Methodology/principal findings This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to determine the state of leishmaniases research in Kenya and identify research gaps. We searched seven online databases to identify articles published until January 2022 covering VL, CL, MCL, and/or PKDL in Kenya. A total of 7,486 articles were found, of which 479 underwent full-text screening, and 269 met our eligibility criteria. Most articles covered VL only (n = 141, 52%), were published between 1980 and 1994 (n = 108, 39%), and focused on the theme of "vectors" (n = 92, 34%). The most prevalent study types were "epidemiological research" (n = 88, 33%) tied with "clinical research" (n = 88, 33%), then "basic science research" (n = 49, 18%) and "secondary research" (n = 44, 16%). Conclusion/significance While some studies still provide useful guidance today, most leishmaniasis research in Kenya needs to be updated and focused on prevention, co-infections, health systems/policy, and general topics, as these themes combined comprised less than 4% of published articles. Our findings also indicate minimal research on MCL (n = 1, <1%) and PKDL (n = 2, 1%). We urge researchers to renew and expand their focus on these neglected diseases in Kenya.